Aristotle vs. Plato: The Balkans' Paradoxical Enlightenment - D. Michalopoulos (University of Sofia, 2007)
As it occurred in West, Aristotle's thought was in Byzantium the main organon of philosophical meditation within the frame of the Christian Faith. Nonetheless, from the ninth century on it was a revival of Platonism that took place - of Neo-Platonism at the beginning and of Platonism itself at the end. The Church, initially indifferent, became suspicious only when, at the turning of the fourteenth to the fifteenth century, the Platonism seemed to engender somewhat a latent paganism; but the Patriarchate was not then able to fight that tendency. So only after the 1453 capture of Constantinople by the Ottomans, Gennadius Scholarius managed to root out from the Greek lands Platonism and its crypto-pagan extension. Be that as it may; the main paradox of the Balkan history is that in the early seventeenth century some leading Greek scholars endorsed the materialist interpretation of Aristotle's thought - as it was taught in the University of Padua by Cesare Cremonini; and as a corollary this materialistic philosophical system began being taught in both Constantinople and Athens. It was that very way that the Enlightenment took birth in the Balkans - and somehow became a State ideology - long before its prevalence in France. And of course all this had as a result a turn toward Physics and Chemistry with far-reaching consequences